The Contribution of Special Events for Territorial Marketing : A Case Study of Luleå Expo - Berg, Jonas; Pääjärvi, Hanna (2011)
The increased competition between cities, regions and countries has led to the development of a relatively new concept known as territorial marketing. These territories compete for investments, resources, labour, residents and tourists etc. In the process of territorial marketing, local activities are coordinated to meet the demand of target customers. In order to sustain the current business and public support as well as attracting new investment, business, tourism or new residents, the territory may need to invest in appealing sub products, such as special events, to help the enhancement of the overall territory as a product. The purpose of this thesis has been to gain a deeper understanding on how special events can be used to constitute a part of territorial marketing. In order to achieve this purpose, a qualitative, single-case study was made on an event management company based in Luleå, Sweden. Data was collected by conducting a face-to-face interview with the project manager of this company. The findings of the study indicate that the hosting of special events can be a way of making the territorial marketing more successful, as the marketing efforts can reach out to a national as well as an international audience. Also, special events bring a direct as well as indirect impact on the local economy. Validerat; 20110617 (anonymous)